1974
DOI: 10.1111/j.1365-2621.1974.tb02899.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Enzymatic Hydrolysis on Some Functional Properties of Whey Protein

Abstract: A study was undertaken to further elucidate the functional properties of whey protein with respect to foaming and emulsifying capacities and to observe the effect of enzymatic hydrolysis on these properties. Emulsion capacity decreased as proteolysis continued suggesting there is an optimum mean molecular size of the proteins involved which is lower than that of casein. Heat treatment of the reconstituted protein concentrate was necessary for foam stability; specific volume and foam stability increased directl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
78
0
4

Year Published

1977
1977
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(89 citation statements)
references
References 4 publications
7
78
0
4
Order By: Relevance
“…Several studies showed decreased foaming stability for protein hydrolysates compared to that of the untreated proteins (Linar es et al, 2000;Klompong et al, 2007;Souissi et al, 2007;Mune, 2015;Zou et al, 2016). Some studies, on the other hand, reported increased foaming capacity of hydrolysates compared to untreated proteins (Kuehler and Stine, 1974;Balti et al, 2010;Mune 2015). An increment in foam capacity due to limited hydrolysis is attributed to more air incorporated into solution of small peptides due to rapid diffusion of peptides to the air-water interface (Kuehler and Stine, 1974;Mune 2015).…”
Section: Foaming Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies showed decreased foaming stability for protein hydrolysates compared to that of the untreated proteins (Linar es et al, 2000;Klompong et al, 2007;Souissi et al, 2007;Mune, 2015;Zou et al, 2016). Some studies, on the other hand, reported increased foaming capacity of hydrolysates compared to untreated proteins (Kuehler and Stine, 1974;Balti et al, 2010;Mune 2015). An increment in foam capacity due to limited hydrolysis is attributed to more air incorporated into solution of small peptides due to rapid diffusion of peptides to the air-water interface (Kuehler and Stine, 1974;Mune 2015).…”
Section: Foaming Propertiesmentioning
confidence: 99%
“…Some studies, on the other hand, reported increased foaming capacity of hydrolysates compared to untreated proteins (Kuehler and Stine, 1974;Balti et al, 2010;Mune 2015). An increment in foam capacity due to limited hydrolysis is attributed to more air incorporated into solution of small peptides due to rapid diffusion of peptides to the air-water interface (Kuehler and Stine, 1974;Mune 2015). However, small peptides do not have the strength required to form stable foams.…”
Section: Foaming Propertiesmentioning
confidence: 99%
“…However, the polypeptides do not have the strength required to give stable foam. The decrease in foam stability manifests itself primarily in the initial 30 min of reaction (Keuhler and Stine 1974). Further hydrolysis is likely to result in peptides, which lack the ability to stabilize the air cells of the foam.…”
Section: Effect Of Enzymatic Modification Of Whey and Casein Protein mentioning
confidence: 99%
“…The peptides that are produced by partial hydrolysis of proteins have smaller molecular size and less secondary structure than the original proteins. The protein solubility, emulsifying properties and foaming properties can be improved with a limited degree of hydrolysis [11][12][13] , whereas excessive hydrolysis often causes loss of some of these functionalities 14) . Protein hydrolysates are widely used as nutritional supplements, functional ingredients and flavour enhancers in foods, coffee whiteners, cosmetics, personal care products, and confectionery, and in the fortification of soft drinks and juices.…”
Section: Introductionmentioning
confidence: 99%